2020
DOI: 10.26682/sjuod.2020.23.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Uav-based Dem for Volume Calculation

Abstract: In the latest decades, Unmanned Aerial Vehicles (UAVs) have witnessed rapid growth and it plays a vital role in different fields of engineering and architecture. This technique can also be applied in land surveying as a device in order to measure the 3D ground coordinates and Earth work. The main aim of this paper is to evaluate the accuracy of volume that obtained by using Digital Elevation Model (DEM) derived from UAVs images. In this research, three different flights were performed with DJI phantom 4 pro (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Other studies, such as those conducted by Idrees and Abdulrahman [60] and Lee and Lee [52], considered estimating the volume of a dam using drone photogrammetry while comparing the results to that produced from the GNSS-RTK method. To ensure accurate volume estimation by the GNSS-RTK, multiple measurements at different locations on the dam were obtained to account for any variations in the shape.…”
Section: Drone Photogrammetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies, such as those conducted by Idrees and Abdulrahman [60] and Lee and Lee [52], considered estimating the volume of a dam using drone photogrammetry while comparing the results to that produced from the GNSS-RTK method. To ensure accurate volume estimation by the GNSS-RTK, multiple measurements at different locations on the dam were obtained to account for any variations in the shape.…”
Section: Drone Photogrammetrymentioning
confidence: 99%
“…To ensure accurate volume estimation by the GNSS-RTK, multiple measurements at different locations on the dam were obtained to account for any variations in the shape. Idrees and Abdulrahman [60] conducted the aerial survey at different flight altitudes, and the error in the estimated volume between the two methods was minor (<0.3%). On the other hand, Lee and Lee [52] showed that the estimated volumes from GNSS-RTK and drone photogrammetry had a difference of 2%.…”
Section: Drone Photogrammetrymentioning
confidence: 99%
“…This information allowed the DTM creation using a set of elevation marks at the nodes of a Triangular Irregular Network (TIN) [32]. As the DTM is built the software allows the volume, real surface area, and a local slope measurements [28].…”
Section: Digital Terrain Model Developmentmentioning
confidence: 99%
“…A DTM is represented as a three-dimensional (3D) raster image that shows the elevations of ground above the mean sea level or above a vertical datum. The UAV-processing platforms methodology, undoubtedly, provides better results than the traditional methods and also requires less time and costs [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the study, it has been determined that the data has been produced at low cost, by saving time and as a result of minimum field work. Idrees et al 32 used the UAV System in their study. In this context, first of all, homogeneously distributed ground control points have been established on the study area (Duhok Dam, Iraq) and the coordinates have been calculated with the help of GNSS receivers.…”
Section: Introductionmentioning
confidence: 99%